OPTIMALISASI MEDIA PEMBELAJARAN ONLINE DALAM MENDORONG KEAKTIFAN BELAJAR SISWA PADA KELAS MATEMATIKA [OPTIMIZATION OF ONLINE LEARNING MEDIA TO ENCOURAGE STUDENTS’ ACTIVE LEARNING IN MATHEMATICS CLASS] - Pasaribu, Misael Hendrivan; Listiani, Tanti (JOHME: Journal of Holistic Mathematics Education, 2021)
The impact of the Covid-19 pandemic requires learning to be done online. That way, the use of technology in the 4.0 era is also needed to be used as an online learning medium. Media that can be used to support online learning are Cisco Webex and educational games such as Quizizz. Observations made by the author of the sixth grade elementary school students show the problem of the lack of active learning of students when participating in online learning. Therefore, the purpose of writing this article is to describe the optimization of online learning media to encourage student learning activities in learning mathematics. The formulation of the problem taken is how to optimize online learning media by teachers in encouraging student learning activities in learning mathematics. The research method used is descriptive qualitative. In addition, in Christian education, teachers must still see each student as the image and likeness of God even though students are less active in participating in online learning. Therefore, teachers still need to pay attention and encourage students to develop and be actively involved in learning. Through the use of Cisco Webex to engage students in discussions and Quizizz to engage students in exercises, students become more active in learning. However, the teacher's efforts have not had an overall impact, so teachers need to understand more about online media and the right features in encouraging student learning activities.BAHASA INDONESIA ABSTRACT: Dampak dari pandemi Covid-19 mengharuskan pembelajaran dilakukan secara online. Dengan begitu, penggunaan teknologi era 4.0 juga diperlukan untuk dijadikan sebagai media pembelajaran online. Media yang dapat digunakan sebagai pendukung dalam pembelajaran online adalah Cisco Webex serta game edukasi seperti Quizizz. Pengamatan yang dilakukan oleh penulis terhadap siswa SD kelas VI menunjukkan masalah kurangnya keaktifan belajar siswa saat mengikuti pembelajaran online. Oleh karena itu, tujuan penulisan artikel ini adalah memaparkan optimalisasi media pembelajaran online untuk mendorong keaktifan belajar siswa di dalam pembelajaran matematika. Rumusan masalah yang diambil adalah bagaimana optimalisasi media pembelajaran online yang dilakukan guru dalam mendorong keaktifan belajar siswa pada pembelajaran matematika. Metode penelitian yang digunakan adalah deskriptif kualitatif.  Selain itu, dalam pendidikan Kristen, guru harus tetap melihat setiap siswa sebagai gambar dan rupa Allah meskipun siswa kurang aktif dalam mengikuti pembelajaran secara online. Oleh karena itu, guru tetap perlu memperhatikan dan mendorong siswa untuk berkembang dan terlibat aktif dalam pembelajaran. Melalui penggunaan Cisco Webex untuk melibatkan siswa dalam diskusi serta Quizizz untuk melibatkan siswa dalam latihan, siswa menjadi lebih aktif mengikuti pembelajaran. Namun upaya guru tersebut belum berdampak secara keseluruhan, sehingga guru perlu memahami lagi media online serta fitur-fitur yang tepat dalam mendorong keaktifan belajar siswa.